THE ROLE OF AI IN REVOLUTIONIZING E-COMMERCE – THE POWER OF DIGITAL MARKETING IN THE MODERN MARKET - Rahayu, Putri; Kholilah, Mela Nur; Khaeroni (Universitas Haji Sumatera Utara, 2025)
The digital revolution has changed the business landscape, and E-commerce is one of the most affected sectors. In recent years, the application of AI in digital marketing has created a revolution in the way businesses either interact with consumers or market products. This article explores the role of Artificial Intelligence (AI) in revolutionizing E-commerce, particularly in digital marketing. Additionally, this article discusses the challenges and opportunities faced by companies in integrating AI into marketing strategies. Through a review using a systematic method of literature review, this research provides insight into how AI can advance E-commerce businesses due to competition in an increasingly dynamic market.